ENVIRONMENTAL AND SOCIAL CONSCIOUSNESS IN SHAPING LOYALTY AMONG INDONESIAN ISLAMIC BANK CUSTOMERS - Ibrahim, Muhammad; Putri, Akmalia Lutfiaturrosyida Agung; Afnani Rosyida; Fitri, Fauziyah; Zahirah, Novri Andini (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
Customer loyalty is important for sustainable development. This research focuses on customers' social and environmental consciousness and how it affects their loyalty to Islamic banking in Indonesia. This research applied a quantitative method. The data analysis used PLS-SEM. The data collecting period was between December 2024 and February 2025. During this period 260 responses were collected using an online questionnaire. The respondents were customers of Islamic banks in Indonesia. Purposive sampling was used to select respondents. Findings show that concern regarding social and environmental issues shapes positive attitudes. Furthermore, attitudes and bank perceptions were found to enhance satisfaction. Likewise, attitudes, perceptions and image of the bank were found to influence loyalty and trust. Self-efficacy moderate of satisfaction and loyalty. Customer satisfaction was found to influence trust and loyalty which is critical to Islamic banks. These findings show Islamic banks the sustainable practices they can undertake that can build loyalty.